A heteropolysaccharide from Rhodiola rosea L.: preparation, purification and anti-tumor activities in H22-bearing mice - Yaru Wu; Qing Wang; Huiping Liu; Lulu Niu; Mengyu Li; Qi Jia (Food Science and Human Wellness)
Numerous polysaccharides isolated from plants have been used to augment traditional drugs in the treatment of cancer. In order to explore the influence to hepatocellular carcinoma, a novel cold water-soluble polysaccharide was separated from Rhodiola rosea L. root (RLP) and then its structure and anti-cancer activities were tested. The chemical compositions and high performance gel permeation chromatography (HPGPC) results indicated that RLP was an acid heteropolysaccharide with the molecular weight of about 1.15×106 Da. Furthermore, ion chromatography (IC), Fourier transform infrared (FT-IR) and nuclear magnetic resoance (NMR) further indicated that RLP was main composed of →2,4)-α-Rha(1→, →5)-α-L-Araf-(1→, α-D-Glu, →6)-β-D-Galp-(1→, β-D-Man and →4)-α-GalpA-(1→. In vivo antitumor activities of RLP were carried out by using H22 tumor-bearing mice model. The results shown that RLP (100 and 300 mg/kg) could inhibit tumor growth of H22 cells from 23.59 % to 45.52 % and protect thymuses and spleen without damage. In addition, according to cell cycle, AV-FITC/PI and JC-1, RLP could induce dose-dependent apoptosis of H22 cells via S phase arrested which was through a mitochondrial related pathway. Our data indicated that RLP has a broader application prospect in anti-tumor preparations.